TUFT1 regulates metastasis of pancreatic cancer through HIF1-Snail pathway induced epithelial–mesenchymal transition. Issue 1 (1st November 2016) - Zhou, Bin; Zhan, Hanxiang; Tin, Lamtin; Liu, Shanglong; Xu, Jianwei; Dong, Yanan; Li, Xiaoyu; Wu, Liqun; Guo, Weidong
Highlights: TUFT1 is overexpressed in PC tissues. TUFT1 is associated with lymph node metastasis and advanced PC stage. TUFT1 promotes PC cell migration and distant metastasis. TUFT1 is associated with expression and activity of HIF1 and Snail. TUFT1 might affect HIF1 – Snail signaling in regulating EMT. Abstract: Pancreatic cancer (PC) is usually lethal because of late diagnosis and early metastasis. Analysis of data from online database showed that TUFT1 is highly expressed in liver metastases of PC, and was associated with shorter overall survival. However, the role of TUFT1 in PC remains unknown. In this study, we show for the first time that TUFT1 is overexpressed in PC tissues compared with adjacent normal pancreas tissues, and TUFT1 expression is significantly associated with lymph node metastasis and advanced PC stage ( P  <   0.05). Depletion or overexpression of endogenous TUFT1 correspondingly inhibited or promoted PC cell migration and metastasis in vitro and in vivo, and affected expression of epithelial–mesenchymal transition (EMT)-related proteins, E-cadherin and vimentin . We also provide evidence that TUFT1 induced EMT by altering the expression of Snail ; that TUFT1 is associated with expression and activity of HIF1 ; and that TUFT1 might affect HIF1 – Snail signaling in regulating EMT. Collectively, these results indicate that TUFT1 could be a novel diagnostic and therapeutic target for PC.